2014
DOI: 10.1074/jbc.m113.511360
|View full text |Cite
|
Sign up to set email alerts
|

βArrestin1 Regulates the Guanine Nucleotide Exchange Factor RasGRF2 Expression and the Small GTPase Rac-mediated Formation of Membrane Protrusion and Cell Motility

Abstract: Background: G protein-coupled receptors (GPCRs) and ␤arrestins have been shown to regulate cell motility. Results: ␤Arrestin1 regulates cell migration through RasGRF2 (a dual guanine nucleotide exchange factor) gene expression and the small GTPase Rac activity. Conclusion: ␤Arrestin1 may regulate cellular functions at the gene expression level. Significance: ␤Arrestins may function at transcriptional and post-translational levels to regulate cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…1G legend for detailed statistics). In a previous study, downregulation of RASGRF2 by 70% with RNAi resulted in a marked decrease of the RASGRF2 protein (30), suggesting that our observed down-regulation can be also significant at the translational level. Crucially, according to ENSEMBL, two protein-coding transcripts are produced from RASGRF2 (RASGRF2-201 and RASGRF2-206; Fig.…”
Section: Artificial Insertion Of the Hk2 Ltr Can Modulate Rasgrf2supporting
confidence: 69%
“…1G legend for detailed statistics). In a previous study, downregulation of RASGRF2 by 70% with RNAi resulted in a marked decrease of the RASGRF2 protein (30), suggesting that our observed down-regulation can be also significant at the translational level. Crucially, according to ENSEMBL, two protein-coding transcripts are produced from RASGRF2 (RASGRF2-201 and RASGRF2-206; Fig.…”
Section: Artificial Insertion Of the Hk2 Ltr Can Modulate Rasgrf2supporting
confidence: 69%
“…The discrepancy of RasGRF2 expression between our results and the previous study is probably due to unelucidated mechanism. Several studies have reported aberrant methylation of RasGRF2 in different cancer, such as pancreatic cancers 27 , non-small cell lung cancer 8 and CRC 10 , which indicated that RasGRF2 expression may be suppressed in these tissues, based on an wide recognition that DNA methylation prevents gene Accumulating evidences suggests that RasGRF2 plays a critical role in movement, invasion and lung colonization of many kinds of cancer cells 5,7,29,30 . RasGRF2 has been shown to suppress rounded movement of melanoma cells 7 , whether RasGRF2 has a role in metastasis of CRC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…RasGRF2 is a multi-domain protein that has dual Ras GEF and Rac GEF activities 4 . The Cdc25 homology domain at the C-terminus catalyzes exchange of GDP to GTP on Ras family proteins 5 . RasGRF2 is involved in regulating NMDA receptor signaling and synaptic plasticity in neuronal tissues 5 and in the control of T-cell proliferation and lymphomagenesis 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also shown that reduced expression of AnxA6 in TNBC cells is associated with increased expression of RasGRF2 (GRF2), a Ca 2+ activated Ras protein specific guanine nucleotide exchange factor (RasGEF) [17], with little effect on other RasGEFs such as SOS1. Meanwhile, GRF2 has been reported to promote cell growth via activation of Ras proteins and to inhibit cell motility via interaction with Cdc42 and Rac1 Rho GTPases [18,19]. Together, these studies suggest that the reciprocal expression of AnxA6 and GRF2 underlies the potential for TNBC cells to either grow rapidly or to become invasive.…”
Section: Introductionmentioning
confidence: 93%